Clinical Retrospective Analysis of 243 Patients with Rhinofacial Ulcers - Ma W; Zhan R; Sui C; Zhou F; Liu H; Zhang X; Ruan Z; Wang Y; Cai X (Dove Medical Press, 2022)
Weiyuan Ma,1 Ruyu Zhan,2 Changlin Sui,3 Fushan Zhou,2 Haidong Liu,4 Xiuwen Zhang,5 Zhenqiang Ruan,6 Yukun Wang,7 Xiaolan Cai8 1Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, Shandong, People's Republic of China; 2Scientific Research Center, Anxi County Hospital, Quanzhou, Fujian, People's Republic of China; 3Department of Dermatology, Yantai Yuhuangding Hospital, Yantai, Shandong, People's Republic of China; 4Department of Dermatology, Liaocheng People's Hospital, Liaocheng, Shandong, People's Republic of China; 5Department of Dermatology, Weihai Municipal Hospital, Weihai, Shandong, People's Republic of China; 6Department of Dermatology, Jinan Dermatosis Prevention and Control Hospital, Jinan, Shandong, People's Republic of China; 7Department of Dermatology, Qilu Hospital of Shandong University, Jinan, Shandong, People's Republic of China; 8Department of Otolaryngology, Qilu Hospital of Shandong University, Jinan, Shandong, People's Republic of ChinaCorrespondence: Weiyuan Ma, Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, Shandong, People's Republic of China, Email fymaweiyuan@wfmc.edu.cnPurpose: The clinical and pathological data of patients with rhinofacial ulcers were retrospectively reviewed and analyzed to lay the foundation for standardized clinical treatment.Patients and Methods: We retrospectively analyzed the clinical data, etiology, pathological features, treatment methods, and prognosis of 243 patients with rhinofacial ulcers treated in the Departments of Otorhinolaryngology and Dermatology at six hospitals in Shandong Province, China from July 2014 to October 2021. The clinical characteristics and treatment methods of the rhinofacial ulcers were summarized to provide a basis for standardizing patients' diagnosis and treatment.Results: The male-to-female ratio of the 243 patients was 2.04:1, and their ages ranged from 25 to 91 years. The most common sites were the cheek, nasal dorsum, and upper lip. The common primary diseases were basal-cell carcinoma, squamous-cell carcinoma, and odontogenic fistula, but rare triggers played important roles in some cases, such as infection, autoimmune diseases, and adverse drug reactions. Surgical treatment was feasible for tumor ulcers; 71 patients with basal-cell carcinoma and 50 with squamous-cell carcinoma were treated with Mohs micrographic surgery. During the follow-up period of 1- 84 months, most of the rhinofacial ulcers were cured, while natural killer/T-cell lymphoma, angiosarcoma, and melanoma were important causes of death.Conclusion: Various causes may lead to rhinofacial skin ulcers, and some cases lacking specificity of clinical manifestations are easily misdiagnosed in clinical practice. Histopathological biopsy is valuable for confirming the diagnosis, after which correct etiological treatment is very important.Keywords: skin, diagnosis, treatment, otorhinolaryngology, dermatology